THE ROLE AND PLACE OF HOSPITAL SURGERY IN THE PRACTICE OF A PEDIATRIC SURGEON - Воробьев, Анатолий Михайлович; Павленко, Владимир Вячеславович; Подолужный, Валерий Иванович; Радионов, Игорь Александрович; Каменева, Евгения Александровна; Старцев, Андрей Борисович (Medicine in Kuzbass, 2025)
The analysis of teaching a course of hospital surgery among students of the Faculty of Medicine and Pediatrics is carried out. The features of the course of surgical diseases in patients, depending on gender, age, and concomitant diseases, including those of congenital origin, have been studied. The forms and optimal timing of surgical treatment have been determined not only for the typical manifestation of the disease, but also for concomitant diseases, as well as for rare forms of surgical pathology.
Keywords: Kemerovo State Medical University; department of hospital surgery; training of surgical personnel